Central planning - Tinbergen, Jan (New Haven ; London : Yale University Press, 1964)
The book is divided into four parts: 1.Economic Planning as Part of the Economic Process: Actors, Task, and Elements. 2.Influence Exerted on the General Economic Process. 3.The Influence of Circumstances and Ideas on the Nature and Intensity of Planning. 4.Optimal Planning.
Includes bibliographical references and index
rpm 24/01/2019
Loans
Keywords: Economics Policy; Economic Planning; Central planning